Using the ecological significance of animal vocalizations to improve inference in acoustic monitoring programs - Wood, Connor M.; Klinck, Holger; Gustafson, Michaela; Keane, John J.; Sawyer, Sarah C.; Gutiérrez, R. J.; Peery, M. Zachariah (Conservation biology, 2021)
Recent bioacoustic advances have facilitated large‐scale population monitoring for acoustically active species. Animal sounds, however, can of information that is underutilized in typical approaches to passive acoustic monitoring (PAM) that treat sounds simply as detections. We developed 3 methods of extracting additional ecological detail from acoustic data that are applicable to a broad range of acoustically active species. We conducted landscape‐scale passive acoustic surveys of a declining owl species and an invasive congeneric competitor in California. We then used sex‐specific vocalization frequency to inform multistate occupancy models; call rates at occupied sites to characterize interactions with interspecific competitors and assess habitat quality; and a flexible multivariate approach to differentiate individuals based on vocal characteristics. The multistate occupancy models yielded novel estimates of breeding status occupancy rates that were more robust to false detections and captured known habitat associations more consistently than single‐state occupancy models agnostic to sex. Call rate was related to the presence of a competitor but not habitat quality and thus could constitute a useful behavioral metric for interactions that are challenging to detect in an occupancy framework. Quantifying multivariate distance between groups of vocalizations provided a novel quantitative means of discriminating individuals with ≥20 vocalizations and a flexible tool for balancing type I and II errors. Therefore, it appears possible to estimate site turnover and demographic rates, rather than just occupancy metrics, in PAM programs. Our methods can be applied individually or in concert and are likely generalizable to many acoustically active species. As such, they are opportunities to improve inferences from PAM data and thus benefit conservation. Uso de la Importancia Ecológica de las Vocalizaciones Animales para Mejorar la Inferencia en los Programas de Monitoreo Acústico Resumen Los avances bioacústicos recientes han facilitado el monitoreo a gran escala de poblaciones de especies acústicamente activas. Sin embargo, los sonidos de animales pueden transmitir cantidades sustanciales de información que queda utilizada insuficientemente en las estrategias comunes de monitoreo acústico pasivo (MAP) que tratan a los sonidos como simples detecciones. Desarrollamos tres métodos de extracción de detalles ecológicos adicionales de los datos acústicos que son aplicables a una gama amplia de especies acústicamente activas. Realizamos censos acústicos pasivos a escala de paisaje para una especie de búho en declinación y para un competidor congenérico invasivo en California. Después utilizamos la frecuencia de vocalizaciones específicas por sexo para orientar los modelos multiestado de ocupación; las tasas de llamados en sitios ocupados para caracterizar las interacciones con los competidores interespecíficos y evaluar la calidad de su hábitat; y una estrategia multivariada flexible para diferenciar a los individuos con base en sus características vocales. Los modelos multiestado de ocupación brindaron estimaciones novedosas para las tasas de ocupación por estado reproductivo que fueron más sólidas ante las detecciones falsas y capturaron el número de asociaciones de hábitat más sistemáticamente que los modelos de estado único agnósticos al sexo. La tasa de llamados estuvo relacionada con la presencia de un competidor pero no con la calidad del hábitat y por lo tanto podría constituir una medida conductual útil para las interacciones que son difíciles de detectar en un marco de trabajo de ocupación. La cuantificación de la distancia multivariada entre los grupos de vocalizaciones proporcionó un medio cuantitativo novedoso para discriminar a los individuos con ≥20 vocalizaciones y una herramienta flexible para balancear los errores del tipo I y del tipo II. Por lo tanto, parecer que hay posibilidad de estimar las tasas demográficas y de rotación, en lugar de sólo las medidas de ocupación, en los programas MAP. Nuestros métodos pueden aplicarse individualmente o de manera conjunta y es probable poder generalizarlas para muchas especies acústicamente activas. Dicho así, son oportunidades para mejorar las inferencias de los datos MAP y por lo tanto, beneficiar a la conservación. 摘要 近年来, 生物声学的发展推动了对叫声活跃物种的大规模种群监测。然而, 动物的声音可以传递大量信息, 这些信息在将声音简单地视为检测信号的被动声学监测的经典方法中还没有得到充分利用。我们开发了三种从声学数据中提取额外生态学细节的方法, 大范围适用于叫声活跃物种。本研究在加利福尼亚对一种数量正在下降的猫头鹰和一种入侵的同类竞争者进行了景观尺度的被动声学调查。我们使用性别特定的发声频率来研究多状态占有模型、在占有位点的鸣叫率 (用于分析与种间竞争者的相互作用和评估生境质量), 以及用一种灵活的多变量方法基于声音特征来区分个体。与不能分辨性别的单一状态占有模型相比, 多状态占有模型对繁殖状态占有率做出了新的估计, 对错误检测更加稳健, 对已知栖息地关联的信息也更加一致。我们还发现, 动物的鸣叫率与竞争者的存在与否有关, 而与栖息地质量无关, 因此可以作为在占有框架中难以检测的互作行为的有效度量标准。鸣叫的组间多变量距离量化为识别超过 20 条声音记录的个体提供了一种新的定量手段, 也是平衡I类错误和II类错误的灵活工具。因此, 我们还有机会在被动声学监测估计位点周转率和种群统计参数, 而不仅仅是占有模型的指标。我们的方法可以单独使用, 也可以协同应用, 且有潜力推广到许多声学活跃的物种中, 从而为改进被动声学监测数据推断提供了机会, 因此有助于保护。【翻译: 胡怡思; 审校: 聂永刚】 Article Impact Statement: Animal sounds are signals, and studying them as such can improve conservation outcomes in passive acoustic monitoring programs.